A manager's guide to participative management - Sashkin, Marshall (New York, N.Y. : AMA Membership Publications Division, American Management Associations, 1982)
The author of this book tries to point out to its readers that, the behavioral sciences offer some hope for dealing more effectively with social complexity. But we must recognize that these are "probability sciences": the knowledge we have gained increases our chances of managing effectively, but does not by any means guarantee this result. No matter how effective a manager's behavior, no matter how well participative management is used, the results will not be perfect and are not guaranteed.
Includes bibliographical references p.88-94.
hza 19/07/2018
Loans
Keywords: Management